ANALISIS TINGKAT PENGANGGURAN DI KABUPATEN BANGGAI TAHUN 2009-2013 - Linggi, Dian; Wiwoho, Bambang (JEB17 : Jurnal Ekonomi dan Bisnis, 2016)
Country indonesia is a developing country in the world,the magnetude of the unemployment rate is very important in assesing the succes of a country. This is because unemployment is one indicator to indicate the level of prosperity of a country as a result of development and economic growth. Population increased followed by increasing the number of labor force will increase the number of unemployed if they are not matched by an increase in employment/jobs. Â As well as cities and districts in indonesia,in Banggai unemployment occurring is quite high,over a period of 5 years from 2009 to 2013 the average unemployment rate of 4,76 percent per year. Unemployment figures are quite disturbing this is an economic phenomena that occurs in Banggai district. The purpose of this studyis to determine labor force and minimum wage wether a significant influence on the unemployment rate in Banggai,and to determine which variable big impact on the unemployment rate. With the result of the research regression F test and T test is known that the number of labor force (X1) and minimum wage (X2) taken together significant effect on unemployment rate in Banggai. From the result RÂ² most dominant variable effect on the unemployment rate is the minimum wageKeywords: unemployment rate, labor force, minimumwage